2014
DOI: 10.2478/hukin-2014-0048
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Match Location, Match Status and Quality of Opposition on Regaining Possession in UEFA Champions League

Abstract: The present study aimed to examine the independent and interactive effects of match location, match status, and quality of opposition on regaining possession, analysed by the type and zone of ball recovery, in matches played in the 2011–2012 UEFA Champions League. Twenty-eight matches of the knockout phase were evaluated post-event using a computerized notational analysis system. Multinomial logistic regression analysis was applied to identify the effects of the previously mentioned situational variables on ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
145
3
13

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(184 citation statements)
references
References 22 publications
23
145
3
13
Order By: Relevance
“…The match location variable influenced independently the possession during the England Premier League 2015/16, i.e., home matches had more possession than away matches (~ 7%). Researches on home advantage in soccer have received more attention in the last years (e.g., 3,8,14,20 ). Different international tournaments have presented home advantage on performance indicators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The match location variable influenced independently the possession during the England Premier League 2015/16, i.e., home matches had more possession than away matches (~ 7%). Researches on home advantage in soccer have received more attention in the last years (e.g., 3,8,14,20 ). Different international tournaments have presented home advantage on performance indicators.…”
Section: Discussionmentioning
confidence: 99%
“…"weak" or "strong" and their position on league rankings), and match status (if winning, losing or drawing) were identified as the most important situational variables that dictates possession patterns [9][10][11][12][13] . Concerning match location, playing home presented stronger interaction with team possession than playing away 6,8,14 , which might be explained by a more familiar environment and a more consistent style of play 15,16 . The quality of opposition is also a determinant variable when investigating possession in soccer 12,16 .…”
Section: Introductionmentioning
confidence: 99%
“…Our results also showed that high-level teams' home and away differences mainly appeared in the variables related to scoring and defending; however, significant differences were observed in most of variables for intermediate-and low-level teams. It may be the reason that, comparing to inferior teams, high-level teams tend to employ more pro-active defensive strategies and they apply more actions aiming directly to recovery the ball from opponent's half of pitch which may lead to more chances of scoring (Almeida et al, 2014). As well, these findings confirmed the conclusion of Lago-Peñas and Lago-Ballesteros (2011, p. 470) that indicated "teams described as superior and those described as inferior did not experience the same home advantage", which is to say that high-level teams' technical and tactical performance is more stable either playing home or away than the intermediate and low level teams.…”
Section: Performance Profiles When Playing At Different Locationsmentioning
confidence: 99%
“…Therefore, the quality of opponent is regarded as a crucial variable determining the performance indicator [12]. Furthermore, home-field advantage is also reckoned as one of situational variables [13,14]. It is well-known that, when playing against the same opponent, winning in the away match reflects a better result than in the home match.…”
Section: Introductionmentioning
confidence: 99%